Carrier dynamics in a 1.55 μm tunneling injection quantum dot semiconductor optical amplifier - Khanonkin, Igor (2020)
Carrier dynamics following a short pulse perturbation in a tunneling-injection quantum dot (QD) gain medium are analyzed. A hybrid state comprising the injection-well and QD first excited state dominate the dynamics with a time constant of 1ps. The role of the perturbation wavelength is discussed.